(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In this article, we have collected the main trends in the field of wireless communication, both current and upcoming years. The latest innovations in the field of wireless communication, RFID (Radio Frequency Identification) technological system components, types, operating ranges, areas of application, as well as existing problems and its role in society are covered in detail.